Selected Nigerian Foods and Vegetables and Their Health Benefits - Famakinwa, Abiodun Olukemi; Obilana, Anthony Olusegun; Oguntibeju , Oluwafemi Omoniyi (Selected Nigerian Foods and Vegetables and Their Health Benefits, 2024)
The book "Selected Nigerian Foods and Vegetables and Their Health Benefits" explores the nutritional aspects of the traditional Nigerian diet, highlighting the advantages of consuming green leafy vegetables and other locally grown foods. This extensive book examines the antioxidant capacity, micronutrient makeup, and possible health benefits of a variety of Nigerian native foods, including peanut soup, amala, rice, moimoi, chinchin, and vegetables like bitter leaf, eggplant, ewedu, egusi, and Lagos spinach. It also offers insightful information on dietary habits and the nutritional contributions of these foods to general well-being. The book helps readers understand the role of staple foods in promoting a healthy lifestyle in the Nigerian context, emphasising both well-known and lesser-known foods. Academic institutions, governmental bodies, and public health organizations must work together to overcome the lack of research on the Nigerian diet. Research on food consumption trends, dietary patterns, nutritional deficiencies, and their links to health outcomes should be supported financially. Data collection techniques and instruments suited to the Nigerian environment should be created and applied to obtain precise dietary data. A thorough understanding of the Nigerian diet is essential for public health policies and interventions to improve nutrition and prevent diet-related diseases.